Adaptation of Directorate General of Taxes employees participating in the Internal Job Vacancy (IJV) program - Solikhatin, Lulus; Utomo, Rachmad (WIM Solusi Prima, 2024)
This research aims to investigate the considerations of employees at the Directorate General of Taxes in participating in the Internal Job Vacancy (IJV) program and their post-placement adaptation practices in the recent workplace. The study adopts a qualitative approach by interviewing individuals who have successfully completed the IJV program and are affiliated with the Directorate General of Taxes. The research describes the various considerations reported by the participants regarding their decision to participate in the IJV program, which are then compared with relevant theories and categorized into four main categories: homebase, passion, organizational policies, and job satisfaction. Furthermore, the research also explores the phenomenon of culture shock and adaptation practices in the recent workplace. The adaptation practices are classified into two categories: job-related and equipment-related adaptation, as well as adaptation with colleagues. Job-related and equipment-related adaptation involves employees participating in training, engaging in self-directed learning, and adopting a